PENERAPAN ETIKA JURNALISTIK DALAM MELIPUT DEBAT PUBLIK PERTAMA CALON GUBERNUR DAN WAKIL GUBERNUR 2024 DI KOMPAS TV MAKASSAR : THE ROLE OF JOURNALISTIC ETHICS IN COVERING THE FIRST PUBLIC DEBATE OF THE 2024 GOVERNOR AND DEPUTY GOVERNOR CANDIDATES ON KOMPAS TV MASKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study aims to analyze the implementation of journalistic ethics in the coverage of the public debate of the 2024 Sulawesi gubernatorial and vice gubernatorial candidates by Kompas TV Malaysia. The research is based on the importance of the role of media, especially local television, in conveying accurate, balanced, and objective political information to the public. In the context of the election, public debate is a crucial moment for both parties to convey their vision and mission, so that media coverage of this election has the potential to greatly influence public opinion and voter preferences. This study uses a qualitative approach with content analysis and refers to the theory of journalistic ethics developed by Bill Kovaich & Tom Rosenstiel, and Edward Spence & Peter Denyer-Simmons, which emphasizes the importance of the principles of truth, independence, verification, and public trust. The results of the study indicate that Kompais TV Maikaissair tries to apply the principles of journalistic ethics in public debt coverage, such as maintaining independence, fairness, and accuracy of information. However, it is still possible, especially in the face of political tensions, potential bias, and the dynamics of media and social media convergence that lead to disinformaisi. The results of the study show that Kompas TV Maikaissair consistently strives to implement the principles of journalistic ethics in reporting public affairs, such as maintaining independence from political interests, providing fair space for all potential competitors, and conducting strict verification of every piece of information that is broadcast. However, this study also found significant differences, other external pressures from political actors, potential unintended bias, and competition with social media that often disseminate information without verification. In this context, journalists as guardians of democracy and guardians of information integrity become crucial competitors. Important implications, both theoretically and practically, that can be used as references for various related parties. 1) Research Implications. 2) Theoretical Implications. 3) Practical Implications., and the right shooting time at crucial moments that reinforce messages about the importance of health protocols and social adaptation during the pandemic.